Mineralocorticoid receptor signaling is implicated in carfilzomib-induced increase in blood pressure. (14th October 2021) - Efentakis, P; Lamprou, S; Makridakis, M; Barla, I; Nikolaou, P.-E; Christodoulou, A; Dimitriou, C; Kastritis, E; Gakiopoulou, C; Gikas, E; Vlachou, A; Thomaidis, N; et al.
Abstract: Introduction: Carfilzomib (Cfz), an irreversible proteasome inhibitor, is a first line antineoplastic agent indicated for relapsed/refractory multiple myeloma, with its clinical use being hampered by cardiovascular adverse effects. Hypertension, is the most common cardiovascular side effect of Cfz, remaining of unknown pathogenicity. Purpose: Considering that management of Cfz-related hypertension remains an unmet clinical need and that renal function plays a pivotal role in blood pressure regulation we sought to investigate the renal contribution in Cfz-induced hypertension. Methods: We have previously established a translational model of Cfz-induced cardiomyopathy, based on clinically applicable dose regimens and we have concluded that two and four dose protocols successfully resemble the clinical observations in vivo. Herein, sixty C57Bl/6 male mice (12–14 weeks old) were randomized to: 1. Two doses Protocol: i. Control (N/S 0.9%), ii. Cfz (8mg/kg) for two consecutive days; and 2. Four doses Protocol: i. Control (N/S 0.9%), ii. Cfz (8mg/kg) for seven days intraperitoneally. Systolic (SBP) and diastolic blood pressure (DBP) were measured by tail cuffs; the latter protocol was repeated and urine collection was performed via metabolic cages studies. Renal samples were collected for histological, proteomic, metabolomic and molecular signaling analyses. Finally, eplerenone, a mineralocorticoid receptor (MR) blocker, was orally co-administered with Cfz to the mice daily (165 mg/kg) in the four doses protocol. Results: Cfz increased SBP only in the four doses protocol (78.50±2.05 vs 68.20±0.73 in the Control group, **P<0.01). Histological evaluation of the kidneys revealed a juxtaglomerular apparatus hyperplasia (JAH) in the same dose regimen. Proteomic analysis presented that metabolic and transport of small molecules pathways were differentially regulated in the Cfz treated murine kidneys. Metabolomic analysis revealed an increase in urea cycle metabolites (L-Alanine, L-Glutamine, glutamate, aspartate) and taurine content in the kidneys. Additionally, mice presented decreased diuresis without any differences in other metabolic parameters. In parallel an upregulation of β-ENaC expression and activation of MR/SGK-1 signaling in the kidneys was observed, indicating that Cfz activates MR signaling. Co-administration of eplerenone and Cfz, restored diuresis, decreased SBP and inhibited MR/SGK-1 signaling in the kidneys. Conclusions: Activation of MR signaling by Cfz in the kidneys orchestrates renal water/salt retention and drives an increase in blood pressure in vivo. Histological and metabolomic analyses present that Cfz induces an acute kidney injury and a tonicity increase. Eplerenone reversed Cfz-induced blood pressure increase and restored diuresis by inhibiting MR/SGK-1 signaling. Therefore, MR blockade emerges as a potent therapeutic approach against Cfz-related cardiovascular adverse events. Funding Acknowledgement: Type of funding sources: None.